P3_6 Would you like some tea? - Patel, Poonam; Patel, Jessica; Joshi, Rutambhara (Physics Special Topics, 2014)
<span style="font-family: 'Calibri','sans-serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This paper investigates the cooling rate of tea under two scenarios, leaving tea to sit by itself and stirring it. The calculation only factors in the heat loss from the top of the cup, neglecting heat loss via conduction through the sides. The results show that stirring the cup of tea would cool it 0.06 times faster than leaving it to cool on its own.